Study Oxidative Stress Statues In Hypertension Women (Baghdad Science Journal, 2016)
The oxidative stress is result of unbalancing between oxidants and antioxidants in the body. Hypertension (HT) is a measure of average systolic blood pressure which created by the heart contracting, greater ?140 mmHg or an average diastolic blood pressure, which is the heart fills, of ?equal to 90 mmHg. The study is conducted on 28 female patients with HT from Ibn Al-nafese hospital in addition to 28 female control. The markers measured are albumin, malondialdehyde (MDA) and 8-Hydroxy deoxyguanosine (8-OHdG). Also electrophoresis study on extracted DNA with Fenton reaction was done. Results of this study show there are high significant decrease (p?0.01) in albumin concentration of patient related to control, and there is a high significant increase (p? 0.01) in each MDA and 8-OHdG for patients group in comparison with controls. The Fenton reaction done shows that oxidant has degradation effect on DNA either in two minutes of reaction. It is concluded that oxidative stress in its parameter (albumin) and markers (MDA and 8-OHdG) is main chemical manifestation of group under study. And oxidants produced by Fenton can denature the DNA in vitro.